TANGGUNG JAWAB BADAN NASIONAL PENCARIAN DAN PERTOLONGAN TERHADAP KORBAN KECELAKAAN PESAWAT UDARA DI INDONESIA (Studi Kasus: Kecelakaan Pesawat Udara Lion Air Nomor Registrasi PK–LQP) - Ang. T. Michella; Amad Sudiro (Jurnal Hukum Adigama, 2019)
Lion Air flight JT610 PK–LQP is the worst airplane accident in 2018, this crashed killed all passengers and crew. The purposes of this research is to examine the responsibilities of National Search and Rescue Agency Republic of Indonesia (BASARNAS) in conducting search and rescue operations for crash victims and how to impose operational costs on search and rescue for these accidents. The method used is the method of normative legal research. Based on research data obtained, the plane crashed was cause by damage of Angle of Attack’s sensor and the aircraft lost its lift power. BASARNAS in this case is responsible for the sense of responsibility, which are required or have any obligation to perform its duties as stated in the decree issued by the government. BASARNAS in conducting search and rescue operations has done their job very well, and in accordance with the provisions of Republic of Indonesia law. Costing search and rescue operations contained in The Republic of Indonesia’s Law number 29 year 2014, the funds from the Indonesian Budget (APBN), Regional Government Budget (APBD), and other funding sources that legitimate and not binding. Search and rescue operations of Lion Air PK–LQP victims conduct by BASARNAS central and used the BASARNAS’s budget, but there were confusion regarding the funds provided for this operation; only BASARNAS issued funds or the airline also provided funds for the operation. As a matter of course aircraft accidents need to form a mandatory insurance rule for search and rescue operations.